Efficacy of Simultaneous Administration of Nimodipine, Progesterone, and Magnesium Sulfate in Patients with Severe Traumatic Brain Injury: A Randomized Controlled Trial - Ali Abdoli (Bulletin of Emergency and Trauma, 2019)
Objective: To investigate the safety and efficacy of simultaneous administration of nimodipine, progesterone, magnesium sulfate in patients suffering from severe traumatic brain injury (TBI).Methods: Overall, 90 patients with blunt head trauma who were admitted to the Besat hospital, Hamadan University of Medical Sciences, Iran through the Emergency Department in 2017 to 2018 were randomly assigned to the study or control groups each containing 45 patients. In the study group, intravenous nimodipine 60 mg every 12 hours for 5 days, intramuscular progesterone 1 mg/kg daily for 5 days, and magnesium sulfate 5 grams stat followed by 2.5 grams every 4 hours for 21 days were administered. Daily GCS and jugular venous oxygen saturation (SjvO2) of the patients were measured on admission day (day 0) through hospitalization day 4 at the intensive care unit. Then, all patients were visited at three months after discharge.Results: The mean age of the patients was 31.4 ± 12.8 years including 59 (65.6%) men with no significant difference between the groups. The baseline GCS and SjvO2 of the patients were comparable in both groups, however, GCS of the patients in the study group were significantly higher in the next 4 hospitalization days compared to the controls. Whereas, the SjvO2 of the patients were not significantly different between the groups during these days. Three-month mortality rate of the patients in the study group was significantly lower than the three-month mortality rate of the patients in the control groups (22.2% vs. 42.2%, p=0.042).Conclusion: Administration of combined protocol of magnesium sulfide, progesterone and nimodipine may be safe and effective in patients suffering from severe TBI.Clinical Trial Registry: IRCT201210229534N2